Pengaruh Strategi Pembelajaran Crossword Puzzle Terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS SMA Negeri 11 Medan Tahun Ajaran 202/2021 - Revita Yuni (Universitas Negeri Medan, 2021)
Abstract: The Effect of Crossword Puzzle Learning Strategies on Economic Learning Outcomes of Class X, Social Studies Students at SMA Negeri 11 Medan in the 2020/2021 Academic Year. This study aims to determine the effect of Crossword Puzzle Learning Strategies on Economic Learning Outcomes of Class X, Social Studies Students at SMA Negeri 11 Medan in the 2020/2021 Academic Year. This research was conducted at SMA Negeri 11 Medan, which is located at Jalan Pertiwi Banten, Medan Tembung No.93 Medan City, North Sumatra. The subjects in this study were students of class X of social studies at SMA Negeri 11 Medan, totaling 72 people consisting of 2 classes. The instrument or data collection technique in this study was a test of learning outcomes in the form of multiple choice as many as 20 questions. The data analysis technique used is the normality test using the Liliefors test, the homogeneity test using the F test, and hypothesis testing with the One Path ANOVA test with the criteria for accepting the hypothesis if it shows a significance value < = 0,05. The results of data analysis obtained the average value of the post-test of experimental class is = 80,139; SD = 10,921. While the post-test of control class is = 70,972; SD = 13,878. Hypothesis testing was carried out using one-way ANOVA with = 0,05. From the hypothesis testing data, the significance value is 0,003 while = 0,05. The results of hypothesis testing indicate that the significance value is < that is 0,003 > 0,05 so that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant influence between the Crossword Puzzle Learning Strategy on the Economics Learning Outcomes of Class X Social Studies Students at SMA Negeri 11 Medan in the 2020/2021 Academic Year. Keyword: Crossword Puzzle Learning Strategies, Learning Outcomes Economic Abstrak: Pengaruh Strategi Pembelajaran Crossword Puzzle Terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS SMA Negeri 11 Medan Tahun Ajaran 202/2021. Penelitian ini bertujuan untuk mengetahui pengaruh Strategi Pembelajaran Crossword Puzzle Terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS SMA Negeri 11 Medan Tahun Ajaran 2020/2021. Penelitian ini dilaksanakan di SMA Negeri 11 Medan yang beralamat di Jalan Pertiwi Banten, Medan Tembung No.93 Kota Medan Sumatera Utara. Subjek dalam penelitian ini adalah siswa Kelas X IPS SMA Negeri 11 Medan yang berjumlah 72 orang yang terdiri dari 2 kelas. Instrumen atau teknik pengumpulan data dalam penelitian ini adalah tes hasil belajar dalam bentuk pilihan berganda sebanyak 20 soal. Teknik analisis data yang digunakan adalah uji normalitas menggunakan uji Liliefors, uji homogenitas menggunakan Uji F, dan uji hipotesis dengan uji Anava Satu Jalur dengan kriteria terima hipotesis apabila menunjukkan nilai Signifikansi < pada = 0,05. Hasil analisis data yang diperoleh nilai rata-rata kelas eksperimen post-tes = 80,139 ; SD = 10,921 Sedangkan kelas kontrol post-test adalah = 70,972 ; SD = 13,878. Pengujian hipotesis dilakukan dengan menggunakan anava satu jalur dengan = 0,05. Dari data pengujian hipotesis nilai Signifikansi sebesar 0,003 sedangkan = 0,05. Hasil pengujian hipotesis menunjukkan bahwa nilai Signifikansi < yaitu 0,003 > 0,05 sehingga H0 ditolak dan Ha diterima. Dengan demikian dapat disimpulkan bahwa ada pengaruh yang signifikan antara Strategi Pembelajaran Crossword Puzzle Terhadap Hasil Belajar Ekonomi Siswa Kelas X IPS SMA Negeri 11 Medan Tahun Ajaran 2020/2021. Kata Kunci : Strategi Pembelajaran Crossword Puzzle, Hasil Belajar Ekonomi.